About the lexical-semantic features of anthroponyms (Texas Journal of Multidisciplinary Studies, 2022)
This article is about the study of anthroponyms, which are lexical units in world and Uzbek linguistics, their lexical-semantic structure, which is one of the important features of the lexical richness of the language. Famous noun and their meanings are also explained, and the use of personal names in positive or negative places is explained.